Molecular and Biological Characterization of a New World Mono-/Bipartite Begomovirus/Deltasatellite Complex Infecting Corchorus siliquosus - Fiallo-Olivé, Elvira; Navas-Castillo, Jesús (Frontiers in Microbiology, 2020)
The genus Begomovirus (family Geminiviridae) is the largest genus in the entire virosphere, with more than 400 species recognized. Begomoviruses are single-stranded DNA plant viruses transmitted by whiteflies of the Bemisia tabaci complex and are considered one of the most important groups of emerging plant viruses in tropical and subtropical regions. Several types of DNA satellites have been described to be associated with begomoviruses: betasatellites, alphasatellites and deltasatellites. Recently, a family of single-stranded DNA satellites associated with begomoviruses has been created, Tolecusatellitidae, including the genera Betasatellite and Deltasatellite. In this work, we have analyzed the population of begomoviruses and associated DNA satellites present in Corchorus siliquosus, a malvaceous plant growing wild in Central America, southeastern North America and the Caribbean, collected in Cuba. Isolates of two New World begomovirus species and two deltasatellite species have been cloned and sequenced from plants showing yellow vein symptoms. Isolates of one of the begomoviruses, Corchorus yellow vein Cuba virus (CoYVCUV), and one of the deltasatellites, Desmodium leaf distortion deltasatellite (DesLDD), represent novel species. Experiments with infectious clones have shown the monopartite nature of CoYVCUV and that DesLDD utilizes the bipartite Desmodium leaf distortion virus as helper virus, but not the monopartite CoYVCUV. Also, CoYVCUV has been shown to infect common bean in addition of Nicotiana benthamiana. This is the first time that (i) a monopartite New World begomovirus is found in a host other than tomato and (ii) deltasatellites have been found in C. siliquosus, thus extending the host and helper virus ranges of this recently recognized class of DNA satellites.